Development of type 2 diabetes following intrauterine growth retardation in rats is associated with progressive epigenetic silencing of Pdx1 - Park, Jun H. (American Society for Clinical Investigation, 2008)

(untitled)
Intrauterine growth retardation (IUGR) has been linked to the onset of diseases in adulthood, including type 2 diabetes, and has been proposed to result from altered gene regulation patterns due to epigenetic modifications of developmental genes. To determine whether epigenetic modifications may play a role in the development of adult diabetes following IUGR, we used a rodent model of IUGR that expresses lower levels of Pdx1, a pancreatic and duodenal homeobox 1 transcription factor critical for β cell function and development, which develops diabetes in adulthood. We found that expression of Pdx1 was permanently reduced in IUGR β cells and underwent epigenetic modifications throughout development. The fetal IUGR state was characterized by loss of USF-1 binding at the proximal promoter of Pdx1, recruitment of the histone deacetylase 1 (HDAC1) and the corepressor Sin3A, and deacetylation of histones H3 and H4. Following birth, histone 3 lysine 4 (H3K4) was demethylated and histone 3 lysine 9 (H3K9) was methylated. During the neonatal period, these epigenetic changes and the reduction in Pdx1 expression could be reversed by HDAC inhibition. After the onset of diabetes in adulthood, the CpG island in the proximal promoter was methylated, resulting in permanent silencing of the Pdx1 locus. These results provide insight into the development of type 2 diabetes following IUGR and we believe they are the first to describe the ontogeny of chromatin remodeling in vivo from the fetus to the onset of disease in adulthood.